Design of Torque and Power Density Improvement According to the Rotor Shape of IPMSM - Lee, Chung-Ho; Noh, Hong-Rae; Kim, Ki-Chan (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In the case of Interior Permanent Magnet Synchronous Motor (IPMSM), it refers to a motor with a structure in which permanent magnets are embedded in the rotor core. Since the permanent magnet has a very low permeability compared to the permeability of the air gap and the magnetic permeability of the Rotor core, the effective air gap of the magnetic flux, depending on the relationship between the d-axis, which is the axis in which the magnetic flux is concentrated, and the q-axis, which is electrically 90degrees ahead of the d-axis, q. In order to reduce the amount of magnetic flux leaking from the shaft, the thickness of the rotor rib is modified and the characteristics are compared according to the experiment.